Particulate composite protective coating using conventional melting approach - Maleque, Md. Abdul; Idris, Nazrin; Rahman, Mohammad M.; Sayeed Hossain, Mohammad (Elsevier, 2020)
The particulate composite protective coating has been developed in thick surface layer on a low alloy steels by preplacing titanium carbide (TiC)different ceramic carbide particles into a shallow melt pool produced on a moving sample using traditional conventional tungsten inert gas (TIG) torch melting approach. Protective layers coating ranging in thickness from 0.05 to 1.0 mm are formed, the thickness being determined by different heat input. The composite protective surface was investigated by a diversity of techniques, including scanning electron microscopy (SEM), energy-dispersive x-ray (EDX) and Microhardness testering. This chapter discusses the types of surface morphology or structures which have been produced by preplacing ceramic TiC particles on the substrate of low alloy steels and TIG melting/particle injection process (so called re-solidification process) and considers the effect on upon these structures developed by different heat input which in turn change the mode of dissolution or particle swimming. Special consideration is given to the degree of hardness development on the particulate composite protective surface after re-solidification via TIG torch melting technique.